2009
DOI: 10.1177/0269216309346546
|View full text |Cite
|
Sign up to set email alerts
|

Costs associated with resource utilization during the palliative phase of care: a Canadian perspective

Abstract: Such results provide a comprehensive picture of costs related to palliative care in Canada, by specifying the cost sharing between the PHCS, the family, and NFPO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
111
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(116 citation statements)
references
References 28 publications
4
111
0
1
Order By: Relevance
“…However, fewer hospitalisations and hospital deaths are likely to have impacts for unpaid family and other carers (Social Care Institute for Excellence, 2013;Newman, 2013;Kelley et al, 2011;McCrone, 2009;Dumont et al, 2009). These may include negative impacts, for example, on carers' mental and physical health or their employment and finances (Funk et al, 2010) and on the total amount of unpaid care…”
Section: Teno Et Al 1997mentioning
confidence: 99%
“…However, fewer hospitalisations and hospital deaths are likely to have impacts for unpaid family and other carers (Social Care Institute for Excellence, 2013;Newman, 2013;Kelley et al, 2011;McCrone, 2009;Dumont et al, 2009). These may include negative impacts, for example, on carers' mental and physical health or their employment and finances (Funk et al, 2010) and on the total amount of unpaid care…”
Section: Teno Et Al 1997mentioning
confidence: 99%
“…[18] Studies that attempted to quantify the proportion of total care costs met by informal caregivers varied widely in their reported costs, with estimates of caregiving ranging from 26.6% -80% of total costs, again with wide variation across different countries. [31,18,34,35 ] It is also worth noting that cost estimates may vary depending on the method used to capture costs. Andersson (2002) reported that the cost of informal care calculated using a ed to 18% to 44% of the cost when a s used.…”
Section: Financial Costs Of Caregivingmentioning
confidence: 99%
“…Canadian-based research led by Dumont has found that the welfare state, the family and not-for-pro t organizations sustained 71.3%, 26.6% and 1.6%, respectively, of all costs associated with end of life care [40]. A recent examination of Canada's Compassionate Care Bene t [41] also suggests that even where bene ts are available, family members can experience challenges in negotiating the system; this study found that family members were concerned about limitations of the bene t, such as strict eligibility criteria and the relative short duration of assistance.…”
Section: E Burdens Of Family Caregiving At the End Of Lifementioning
confidence: 99%